Treatment of Agricultural Wastewater with Chlorpyrifos by Coupling of Heterogeneous Photocatalysis and Anaerobic Biological Process (2020)
Treatment of wastewater with Chlorpyrifos content using heterogeneous photocatalysis was evaluated, for which a compound parabolic collector (CPC) was used, under diferent combinations of pH and TiO2 concentration designed using the response surface methodology (RSM), and an anaerobic biological process based on the specifc methanogenic activity test (SMA), using a focculent sludge and an initial concentration of 2.0 g VSS/L. Initially, water resulting from the triple washing of equipment for manual application of Chlorpyrifos from the El Zulia Irrigation District and the municipality of Bucarasica were characterized. In the biological process, COD and TOC removals of 46.4% and 86.6% were obtained; while by applying preliminary photocatalytic processes, under optimal conditions of TiO2 (100 mg/L), pH (3 units) and retention time (3 h), better biodegradability efciencies (72.2% and 53.0%) were achieved. The results revealed that the combined use of advanced oxidation processes with biological treatment technologies is technically viable, as it increases the efciency of removing contaminants from agricultural efuents with Chlorpyrifos.